The Taboo of Performing Wayang Puppet in Arcawinangun, East Purwokerto (Paramita: Historical Studies Journal, 2022)
This research aims to uncover the taboo of performing wayang puppets in Arcawinangun, Banyumas Regency. The research method uses the historical method. Heuristics are carried out by collecting folklore data processed through external and internal criticism to obtain intellectual historical facts at the local level. This fact is interpreted concerning local wisdom, which produces Banyumas’ intellectual historiography. People of Arcawinangun deem the story of the birth of sacred Parikesit and feel the trauma of the effect of the war of the Bharatas or Bharatayuda. The battle depicts the cruelty and violence causing family members to become victims. To forget it, people create a non-sacred story known as carangan. Bharatayuda passed down sins through murders justified by swear and curses. The war caused the annihilation of the Kauravas, followed by that of the Pandavas. The Pandavas indeed remain intact, but they lost their offspring. Tujuan penelitian ini mengungkap tabu pertunjukan wayang kulit di Arcawinangun kabupaten Banyumas. Metode penelitian menggunakan metode sejarah. Heuristik dilakukan dengan mengumpulkan data folklore yang diproses melalui kritik ekstern dan intern sehingga diperoleh fakta sejarah inteletual di tingkat lokal. Fakta tersebut diinterpetasikan dengan acuan kearifan lokal yang menghasilkan historiografi intelektual Banyumas. Hasil penelitian tentang tabu pertunjukan wayang pada masyarakat Arcawinangun bersumber dari kisah cerita kelahiran Parikesit dan perang Bharatas atau Bharatayuda yang memunculkan trauma. Pertempuran tersebut menggambarkan kekejaman dan kekerasan yang menyebabkan anggota keluarga menjadi korban. Untuk melupakannya, orang membuat cerita non-sakral yang dikenal sebagai carangan. Bharatayuda menurunkan dosa melalui pembunuhan yang dibenarkan dengan sumpah dan kutukan. Perang menyebabkan pemusnahan Kurawa diikuti oleh Pandawa. Pandawa memang tetap utuh, tetapi mereka kehilangan keturunannya. Cite this article: Priyadi, S. Kosasih, A.D., Nugroho, A.S. (2022). The Taboo of Performing Wayang Puppet in Arcawinangun, East Purwokerto. Paramita: Historical Studies Journal, 32(2), 230-242. http://dx.doi.org/10.15294/paramita.v32i2.37834